Sterol, Glycerol Ester, and Thiophene Constituents from the Twigs of Pluchea indica L. of Vietnam - Giang, Phan Minh; Huyen, Van Thi Thanh; Huong, Do Thi Viet (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4749, 2018)
The first study of the twigs of Pluchea indica L. in Vietnam isolated stigmasterol, 1- eicosanoyl glycerol, a long-chain saturated alcohol, 2-(prop-1-ynyl)-5-(5,6-dihydroxyhexa-1,3- diynyl)-thiophene, stigmasterol 3-O-β-D-glucopyranoside, and β-sitosterol 3-O-β-D-glucopyranoside. Their structures were determined on the basis of MS and NMR spectroscopic data. Keywords Pluchea indica, Asteraceae, sterol, glycerol ester, thiophene References [1] Đỗ Tất Lợi (2014), Những cây thuốc và vị thuốc Việt Nam, Nhà xuất bản Hồng Đức, Hà Nội. [2] Qiu Y. Q., Qi S. H., Zhang S., Tian X. P., Xiao Z. H., Li M. Y., Li Q. X. (2008). Heterocycles, 75, 1757-1764. [3] Buapool D., Mongkol N., Chantimal J., Roytrakul S., Srisook E., Srisook K. (2013). J. Ethnophamacol., 146, 495-504. [4] Noridayu A. R., Hii Y. F., Faridah A., Khozirah S., Lajis N. (2011). Int. Food Res. J., 18, 925-929. [5] Cho J. J., Cho C. L., Kao C. L., Chen C. M., Tseng C. N., Lee Y. Z., Liao L. J., Hong Y. R. (2012). BMC Complement. Altern. Med., 12, 265. [6] Kao C. L., Cho J., Lee Y. Z., Cheng Y. B., Chien C. Y., Hwang C. F., Hong Y. R., Tseng C. N., Cho C. L. (2015). Molecules, 20, 11508-11523. [7] Uchiyama T., Miyase T., Ueno A., Usmanghani K. (1991). Phytochemistry, 30, 655-657. [8] Hussain H., Al-Harrasi A., Abbas G., Rehman N. U., Mabood F., Ahmed I., Saleem M., van Ree T., Green I. R., Anwar S., Badshah A., Shah A., Ali I. (2013). Chem. Biodivers, 10, 1944-1971. [9] Ohtsuki T., Yokosawa E., Koyano T., Preeprame S., Kowithayakorn T., Sakai S., Toida T., Ishibashi M. (2008). Phytother. Res., 22, 264-266. [10] Gomes A., Saha A., Chatterjee I., Chakravarty A. K. (2007). Phytomedicine, 14, 637-643. [11] Biswas R., Dutta P. K., Achari B., Bandyopadhyay D., Mishra M., Pramanik K. C., Chatterjee T. K. (2007). Phytomedicine, 14, 534-537. [12] https://pubchem.ncbi.nlm.nih.gov/compound. [13] Biswas R., Dasgupta A., Mitra A., Roy S. K., Dutta P. K., Achari B., Dastidar S. G., Chatterjee T. K. (2005). Eur. Bull. Drug Res. 13, 63-70. [14] Kaur N., Chaudhary J., Jain A., Kishore L. (2011). IJPSR, 2, 2259-2265.